Inter‐individual and inter‐regional variations in enteric drug metabolizing enzyme activities: Results with cryopreserved human intestinal mucosal epithelia (CHIM) from the small intestines of 14 donors. Issue 5 (26th August 2020) - Li, Albert P.; Ho, Ming‐Chih D.; Alam, Novera; Mitchell, Walter; Wong, Susan; Yan, Zhengyin; Kenny, Jane R.; E. C. A. Hop, Cornelis
Abstract: We have previously reported successful isolation and cryopreservation of human intestinal mucosa (CHIM) with retention of viability and drug metabolizing enzyme activities. Here we report the results of the quantification of drug metabolizing enzyme activities in CHIM from different regions of the small intestines from 14 individual donors. CHIM were isolated from the duodenum, jejunum, and ileum of 10 individuals, and from 10 consecutive 12‐inch segments starting from the pyloric sphincter of human small intestines from four additional individuals. P450 and non‐P450 drug metabolizing enzyme activities (CYP1A2, CYP2A6, CYP2B6, CYP2C8, CYP2C9, CYP2C19, CYP2D6, CYP2E1, CYP3A, UGT, SULT, FMO, MAO, AO, NAT1, and NAT2) were quantified via incubation with pathway‐selective substrates. Quantifiable activities were observed for all pathways except for CYP2A6. Comparison of the duodenum, jejunum, and ileum in 10 donors shows jejunum had higher activities for CYP2C9, CYP3A, UGT, SULT, MAO, and NAT1. Further definition of regional variations with CHIM from ten 12‐inch segments of the proximal small intestine shows that the segments immediately after the first 12‐inch segment (duodenum) had the highest activity for most of the drug metabolizing enzymes but with substantial differences among the four donors. Our overall results demonstrate that there are substantial individual differences in drug metabolizing enzymes and that jejunum, especially the regions immediately after the duodenum, had the highest drug metabolizing enzyme activities.